Assessment of extracting molars and premolars after root canal treatment: A retrospective study - Mazen Almasri (Saudi Dental Journal)
Background: The loss of dentition after root canal treatment is a multifactorial entity which might differ between different teeth. The extraction can be more critical, as well as the rehabilitation options. Aim: To analyze if the etiology of extracting root canal treated teeth is different between premolars and molars. Materials and methods: The study included a total of 403 cases with non-surgical root canal therapy (NSRCT) and crown coverage that was referred to the oral surgery clinic for extraction. Tooth type, patient’s age, gender, time since treatment completion, and the reason for extractions were recorded and analyzed. Results: The most frequently extracted teeth were molars (55.6%), followed by premolars (30.3%) and anterior teeth (14.1%). The reasons for extraction were subgingival decay (SGD) (62.5%), vertical root fractures (VRF) (25.3%), and patient demands after uncomfortableabscess discharge (12.2%). Most of the teeth survived between 13 and 36 months after NSRCT. The statistical power of 0.92 was demonstrated, and a P-value of less than 0.05 presented significant correlations. Conclusion: Molars were extractedafter NSRCT due to SGD followed by premolars, which were extracted due to VRF. Special care should be taken while planning NSRCT treatment for molars, in particular, with emphasis on the importance of oral hygiene and follow-up visits. Keywords: Extraction, Root canal treatment, Vertical root fracture, Caries, Survival